Automated Software Testing for Multi Platform Applications using Katalon - Suhatati Tjandra; Indra Maryati; Joshua Theopilus (Widya Teknik, 2021)
The testing process is not only useful for testing existing features, but also for finding errors on websites and mobile applications. It also provides feedback to the developer about the application being tested. To test large scale applications, a test automation is needed so that testing can be done more efficiently and effectively. Katalon Studio is an automation testing tool developed by Katalon LLC to automate testing on websites, API's and mobile applications. The programming languages used to create scripts in Katalon Studio are Groovy, Java, and Javascript. The scripting technique provided by Katalon Studio is a keyword driven approach where keywords in the method of Katalon Studio are used to represent the actions performed by tester on the application being tested. Katalon Studio will also facilitate tester in documenting testing results or test reports in the form of charts, graphs, and detailed reports using Katalon Analytics. The results of the testing show that the use of Katalon Studio helps both beginner and experienced tester create and design automation testing on websites, APIs, and mobile applications with spy and record utilities features. Katalon Studio also provides interactive test reports in the form of graphic visualization. From the results of API testing, it can be concluded that Katalon Studio makes it easy for tester to do end to end API testing without additional integration with other software.